2017
DOI: 10.18203/2319-2003.ijbcp20170347
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study to evaluate the anti-inflammatory effect of moringa oleifera leaves in animal models

Abstract: Background: Inflammatory diseases are a major cause of morbidity and disability of work force throughout the world. The treatment of inflammation with standard steroidal and non-steroidal anti-inflammatory drugs shares the risk of toxicity on various organ systems. Moringa oleifera, an herbal plant has been claimed to be effective in the treatment of various types of inflammatory conditions. However, there is lack of scientific studies to ratify these claims. Therefore, the present study was undertaken to expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…The various active constituents present in the aqueous extract are responsible for inhibiting monocyte infiltration and fibroblast proliferation, which causes an anti-inflammatory effect. Pro-inflammatory cytokines produced by active monocytes trigger the TNF-α to enhance the inflammation of the cells by increasing endothelial cell adhesion of the neutrophils and lymphocytes [ 135 ]. Sharma and Singh [ 62 ] reported that 95% ethanolic leaf extract inhibits oedema development in carrageenan-induced paw oedema in albino mice at a dose of 1000 mg/kg body weight and reduces it by 79% after 5 h compared to the standard drug diclofenac sodium.…”
Section: Health Benefits Of Moringa Oleifera Leavesmentioning
confidence: 99%
See 1 more Smart Citation
“…The various active constituents present in the aqueous extract are responsible for inhibiting monocyte infiltration and fibroblast proliferation, which causes an anti-inflammatory effect. Pro-inflammatory cytokines produced by active monocytes trigger the TNF-α to enhance the inflammation of the cells by increasing endothelial cell adhesion of the neutrophils and lymphocytes [ 135 ]. Sharma and Singh [ 62 ] reported that 95% ethanolic leaf extract inhibits oedema development in carrageenan-induced paw oedema in albino mice at a dose of 1000 mg/kg body weight and reduces it by 79% after 5 h compared to the standard drug diclofenac sodium.…”
Section: Health Benefits Of Moringa Oleifera Leavesmentioning
confidence: 99%
“…Moringa extract showed comparable results with 25.19% and 47.18% inhibition of carrageenan- and formaldehyde-induced paw oedema, respectively, and 41.48% inhibition of cotton pellet induced granuloma as compared to dexamethasone with 28.64%, 54.45%, and 58.71% inhibition. The presence of several active secondary metabolites and the release of mediators in all phases could be a possible reason for such anti-inflammatory action [ 135 ].…”
Section: Health Benefits Of Moringa Oleifera Leavesmentioning
confidence: 99%
“…Moringa has long been suggested to possess some anti-inflammatory properties [11] and murine studies using Moringa leaves have shown a significant reduction in experimentally induced inflammation [40]. The immune response to malaria is characterized by a robust Th1 inflammatory response [41].…”
Section: Discussionmentioning
confidence: 99%
“…A biochemical safety study on the micro and macronutrients present in Moringa was performed by Asiedu-Gyekye and colleagues using an in vivo murine model [47]. In their studies to access the macromolecules, they treated mice with a subacute single dose of 5000 mg/ kg and a range of 0 mg/kg to 1000 mg/kg (40,80,200, and 1000 mg/kg) for 14 days. White blood cell counts increased by 52.5% compared to controls in their single high dose as well as in their 40 mg/kg and 80 mg/kg dosages [47].…”
Section: Discussionmentioning
confidence: 99%
“…Aqueous extracts of Moringa oleifera leaves possess anti-inflammatory activity. [33] The phytochemicals like phenolic acids and flavanols present in Moringa are associated with its anti-inflammatory effect. [30,42] Anticancer Activity Moringa can be used as an anticancer agent as it is natural, reliable and safe, at established concentrations.…”
Section: Antiinflammatory Activitymentioning
confidence: 99%